A COMPARATIVE STUDY ON THE EFFECTS OF SILVER AND ZINC OXIDE NANOPARTICLES ON GERMINATION AND MORPHOLOGICAL TRAITS OF MODIFIED MARIGOLD PLANTS - Yadav, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study focuses on the effects AgNPs and ZnONPs have on germination and the looks of genetically modified marigold (Tagetes spp.) plants. Because agriculture is now looking more into nanotechnology, scientists are finding out how nanoparticles may boost seed planting, plant development and harvested crops. Different concentrations of AgNPs and ZnONPs were used with modified seeds in this study, and scientists observed how much they influenced germination, root and shoot growth, solution Vigor index, and the seedlings dry weight. Based on the findings, scientists can see how each nanoparticle stands out in affecting plant evolution, bringing new ideas for eco-friendly and nanotechnology-based farming.